Urinary Aromatic Amino Acid Metabolites Associated With Postoperative Emergence Agitation in Paediatric Patients After General Anaesthesia: Urine Metabolomics Study - Li, Yueyue; Li, Jingjie; Shi, Yuhuan; Zhou, Xuhui; Feng, Wanqing; Han, Lu; Ma, Daqing; Jiang, Hong; Yuan, Yongfang (Frontiers in Pharmacology, 2022)
Background: Emergence agitation (EA) is very common in paediatric patients during recovery from general anaesthesia but underlying mechanisms remain unknown. This prospective study was designed to profile preoperative urine metabolites and identify potential biomarkers that can predict the occurrence of EA. Methods: Two hundred and twenty-four patients were screened for recruitment; Of those, preoperative morning urine samples from 33 paediatric patients with EA and 33 non-EA gender and age matched patients after sevoflurane general anaesthesia were analysed with ultra-high-performance liquid chromatography (UHPLC) coupled with a Q Exactive plus mass spectrometer. Univariate analysis and orthogonal projection to latent structures squares-discriminant analysis (OPLS-DA) were used to analyze these metabolites. The least absolute shrinkage and selection operator (LASSO) regression was used to identify predictive variables. The predictive model was evaluated through receiver operating characteristic (ROC) analysis and then further assessed with 10-fold cross validation. Results: Seventy-seven patients completed the study, of which 33 (42.9%) patients developed EA. EA and non-EA patients had very differences of the preoperative urine metabolic profiling. Sixteen metabolites including 9 aromatic amino acids metabolites, acylcarnitines, pyridoxamine, porphobilinogen, 7-methylxanthine and 5'-methylthioadenosine were found associated with an increased risk of EA, and they all exhibited the higher levels in EA group than in non-EA group. The main metabolic pathways involved in these metabolic changes included phenylalanine, tyrosine and tryptophan metabolisms. Among these potential biomarkers, L-tyrosine had the best predictive value with an odds ratio (OR) (95% CI) of 5.27 (2.20–12.63) and the AUC value of 0.81 (0.70-0.91) and was robust with internal 10-fold cross validation. Conclusions: Urinary aromatic amino acid metabolites are closely associated with EA in paediatric patients and further validation with larger cohorts and mechanistic study are needed.